The diagnostic methods in the COVID-19 pandemic, today and in the future. (1st September 2020) - Wu, So Yat; Yau, Hoi Shan; Yu, Man Yee; Tsang, Hin Fung; Chan, Lawrence Wing Chi; Cho, William Chi Shing; Shing Yu, Allen Chi; Yuen Yim, Aldrin Kay; Li, Marco J W; Wong, Yin Kwan Evelyn; Pei, Xiao Meng; Cesar Wong, Sze Chuen
ABSTRACT: Introduction: The emergence of anovel coronavirus identified in patients with unknown cause of acute respiratory disease in Wuhan, China at the end of 2019 has caused aglobal outbreak. The causative coronavirus was later named as severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) and the disease caused by SARS-CoV-2 was named as Coronavirus Disease-2019 (COVID-19). As of 10 August 2020, more than 19, 718, 030 confirmed cases and 728, 013 deaths have been reported. COVID-19 is spread via respiratory droplets which are inhaled into the lungs. Areas covered: In this article, we summarized the knowledge about the causative pathogen of COVID-19 and various diagnostic methods in this pandemic for better understanding of the limitations and the nuances of virus testing for COVID-19. Expert opinion: In this pandemic, rapid and accurate identification of COVID-19 patients are critical to break the chain of infection in the community. RT-PCR provides a rapid and reliable identification of SARS-CoV-2 infection. In the future, molecular diagnostics will still be the gold standard and next-generation sequencing can help us to understand more on the pathogenesis and detect novel mutations. It is believed that more sophisticated detection methods will be introduced to detect SARS-CoV-2 as earliest as possible.